Manual de clasificación de puestos y un reglamento de admisión y empleo para el talento humano de la empresa distribuidora Fagi Cia. Ltda. De la ciudad de Loja, provincia de Loja - Granda Torres, Nancy Lorena (2014)
This Investigative work entitled MANUAL CLASSIFICATION OF POSTS AND REGULATION OF ADMISSION AND EMPLOYMENT FOR HUMAN TALENT COMPANY DISTRIBUTOR FAGI CIA. LTDA. CITY OF LOJA, Loja Province, aims to establish the technical guidelines to be applied by the administrative part in the allocation of functions of each member of the company, so that the implementation of a regulation is necessary and admission employment, which allows to have the right people for the jobs are there. To meet the objectives, it was necessary to use research methods such as: Inductive Method Deductive and Analytical, through which it was inferred and analyzed the views expressed by the manager and interviewed workers and respondents respectively, determining the organization of the institution as well as their positions. The techniques used were direct observation, interview and survey manager 34 workers, these techniques allowed to determine the business environment, confronting reality exists on talent management and a clear and broad knowledge of administrative management . Below is a History of the distributor which also exposed the macro and micro localization and the previous chart was made. Then the results of the surveys conducted as well as the interview with the manager of the company are set, which provides valuable information on the functions currently serving employees of the company and the process of admission and employment. In discussing the new mission and vision of the distributor and the new organizational structure is proposed, which in turn determines the proposed manual functions, after which the process of admission and employment FAGI will be proposed. The following conclusions have been established, among which the most important are: • The organizational structure that had the company was obsolete by the new requirements of the company and the market. • The FAGI distributor does not have at present manual functions • The distributor FAGI Cia. Ltda. Does not have a proper process of admission and employment And the most important recommendations were: • Set the manual functions proposed through this research into practice. • Run the rules for admission and employment for personnel selection. Finally the bibliography and appendices consist of work where they have established some examples of tests that serve as the basis for the process of admission and employment.